Anatomy of a business plan : the step-by-step guide to building a business and securing your company's future - Pinson, Linda (Out of Your Mind...and into the Marketplace, 2014)
"Used by more than 1.5 million business owners since its original publication, the new edition of this classic how-to guide provides any entrepreneur the tools to create a well-constructed business plan. All steps are included--from initial considerations to envisioning the organizational structure to creating a growth-powering marketing plan and building for the future with airtight financial documents. The book offers proven, step-by step advice for developing and packaging the components of the plan and keeping them up to date, including cover sheets, table of contents, executive summary, organization and marketing plans, and financial and supporting documents. Five real-life business plans and blank forms and worksheets provide readers with additional user-friendly guidelines for the creation of the plans. The revisions included in the new edition include updated chapters on writing a marketing plan and financing resources as well as a new, complete example of a business plan for a nonprofit organization"--Publisher's description.